2004
DOI: 10.1556/sscmath.41.2004.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Planar point sets with a small number of empty convex polygons

Abstract: A subset A of a finite set P of points in the plane is called an empty polygon, if each point of A is a vertex of the convex hull of A and the convex hull of A contains no other points of P. We construct a set of n points in general position in the plane with only ˜1.62n2 empty triangles, ˜1.94n2 empty quadrilaterals, ˜1.02n2 empty pentagons, and ˜0.2n2 empty hexagons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 8 publications
1
56
0
Order By: Relevance
“…Concerning empty convex four-gons, Bárány and Füredi [7] established that f 4 (n) is of order Θ(n 2 ), and the currently best bounds on f 4 (n) are [2,9]. Research mainly focussed on empty convex polygons.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning empty convex four-gons, Bárány and Füredi [7] established that f 4 (n) is of order Θ(n 2 ), and the currently best bounds on f 4 (n) are [2,9]. Research mainly focussed on empty convex polygons.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the lower bounds cannot be super-quadratic, as has been noted in several papers [5,8]. The construction with the best upper bounds is due to Bárány and Valtr [5]; it produces n-point sets with roughly 1.62n 2 empty triangles, 1.94n 2 empty convex quadrilaterals, 1.02n 2 empty convex pentagons, and 0.2n 2 empty convex hexagons.…”
Section: Introductionmentioning
confidence: 91%
“…The construction with the best upper bounds is due to Bárány and Valtr [5]; it produces n-point sets with roughly 1.62n 2 empty triangles, 1.94n 2 empty convex quadrilaterals, 1.02n 2 empty convex pentagons, and 0.2n 2 empty convex hexagons. Both constructions in [5,8] use Horton's construction as the main building block.…”
Section: Introductionmentioning
confidence: 99%
“…For the case of empty triangles, Katchalski and Meir [11] showed that f 3 (n) is of order Θ(n 2 ). Later, this bound has been refined [2,6,7,8,9,13]; the currently best bounds are n 2 − 32n…”
Section: Theorem 01 E [N 4 ] = θ(N 2 Log N)mentioning
confidence: 99%
“…Concering empty convex four-gons, Bárány and Füredi [6] established that f 4 (n) is of order Θ(n 2 ), and the currently best bounds on [2,7]. Research mainly focussed on empty convex polygons.…”
Section: Theorem 01 E [N 4 ] = θ(N 2 Log N)mentioning
confidence: 99%